2014
DOI: 10.1002/anie.201403556
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Kinetic Resolution of Unprotected β‐Substituted β‐Amino Acids Using Recyclable Chiral Ligands

Abstract: The first chemical method for resolution of N,C-unprotected β-amino acids was developed through enantioselective formation and disassembly of nickel(II) complexes under operationally convenient conditions. The specially designed chiral ligands are inexpensive and can be quantitatively recycled along with isolation of the target β-substituted-β-amino acids in good yields and excellent enantioselectivity. The method features a broad synthetic generality including β-aryl, β-heteroaryl, and β-alkyl-derived β-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 50 publications
1
54
0
1
Order By: Relevance
“…In spite of a number of highly creative asymmetric methods for making enantioenriched β-amino acids (26, 27), resolution is still frequently utilized due to the ease of preparing racemic β-amino acids by the Rodionov reaction. The development of highly efficient catalysts to resolve racemic β-amino acids continues to attract significant attention (2830). Using our methodology, β-phenyl-β-amino acid 4a is iodinated under the standard conditions to give 6a with excellent selectivity ( s , 128).…”
mentioning
confidence: 99%
“…In spite of a number of highly creative asymmetric methods for making enantioenriched β-amino acids (26, 27), resolution is still frequently utilized due to the ease of preparing racemic β-amino acids by the Rodionov reaction. The development of highly efficient catalysts to resolve racemic β-amino acids continues to attract significant attention (2830). Using our methodology, β-phenyl-β-amino acid 4a is iodinated under the standard conditions to give 6a with excellent selectivity ( s , 128).…”
mentioning
confidence: 99%
“…Literature survey revealed that, acid impurity III, alkene impurity IV and enantiomer impurity VI are known in the prior art. Acid impurity III and alkene impurity IV were reported as sitagliptin intermediates,–,, as well as degradation products whereas cyclohexyl impurity V hitherto not known in the prior art.…”
Section: Resultsmentioning
confidence: 99%
“…− So far, many approaches are reported for the synthesis of the acid impurity III, some have used expensive chiral ligand based catalyst ( S )‐binapRuCl 2 to accomplish the stereo selective reduction of methyl 3‐oxo‐4‐(2,4,5‐trifluorophenyl)butanoate, subsequently Mitsunobu reaction to obtain acid impurity III . Other methods employs asymmetric hydrogenation by using [Rh(COD)Cl] 2 in presence of chiral ferrocenyl ligand to accomplish asymmetric transformation, most of the procedures uses either expensive enzymes,– expensive chiral catalyst 2 R (+)DIP‐Cl or use of expensive chiral ligands ,,. One of the route among all the reported synthetic routes for acid impurity III is depicted in Scheme a which follows lengthier synthetic procedure and employs enzymatic resolution of 13 with α ‐chymotrypsin and final step involves use of hazardous diazomethane and costlier silver acetate to obtain amino acid with an overall 40% yield.…”
Section: Resultsmentioning
confidence: 99%
“…[19] In this work, we report that with the fully recyclable ligands 3,t he DKR of unprotected TM-a-AAs proceeds with virtually complete stereoselectivity under operationally simple and convenient reaction conditions.F urthermore,t he present method has broad synthetic generality,a nd can be applied to most challenging,s terically constrained substrates with tertiary side chains.T hese features,incombination with the very low cost of the recyclable ligands 3,b ode well for their wide application for the practical preparation of enantiomerically pure TM-a-AAs of academic and pharmaceutical importance. [19] In this work, we report that with the fully recyclable ligands 3,t he DKR of unprotected TM-a-AAs proceeds with virtually complete stereoselectivity under operationally simple and convenient reaction conditions.F urthermore,t he present method has broad synthetic generality,a nd can be applied to most challenging,s terically constrained substrates with tertiary side chains.T hese features,incombination with the very low cost of the recyclable ligands 3,b ode well for their wide application for the practical preparation of enantiomerically pure TM-a-AAs of academic and pharmaceutical importance.…”
mentioning
confidence: 84%